New Insights in Pathogenesis of Endometriosis - Signorile, Pietro G.; Viceconte, Rosa; Baldi, Alfonso (Frontiers in Medicine, 2022)
Endometriosis is a gynecological disease characterized by the growth of endometrial glands and stroma outside the uterine cavity. The incidence of the disease is very high, there are currently no reliable early diagnostic tests, the therapies are only symptomatic and, consequently, the social impact of endometriosis is very important, also considering the related fertility problems. Despite this, the pathogenesis of endometriosis is still not fully defined. Retrograde menstruation and coelomic metaplasia are currently the most recognized pathogenetic hypotheses. Recent experimental evidences generated by our research group and by others have indicated an alteration of the fine-tuning of the female genital system developmental program during a critical window of time in the fetal life as the pathogenetic event prompting to the development of endometriosis later in life. Goal of this article is to present a revision of the recent literature about the different pathogenetic mechanisms proposed for endometriosis with particular emphasis on the embryologic theory. The possible clinical and pathological implications of these findings will be discussed.